PENERAPAN MODEL POE (PREDICTION, OBSERVATION,EXPLANATION) UNTUK MENINGKATKAN KETERAMPILAN PROSES DAN HASIL BELAJAR IPA SISWA KELAS VIII SMP NEGERI 14 PEKANBARU - Dewi, Indah Permata; Arnentis, Arnentis; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Research in SMP N 14 Pekanbaru has been conducted in November to December 2018 which aims to improve students' science process and learning outcomes through the application of the POE Model (Prediction, Observation, Explanation) in class VIII of SMP N 14 Pekanbaru using the class action research method PTK). the subjects in this study were students of class VIII-6, amounting to 37 students. The instruments used were learning devices, test sheets and observation sheets. The data was obtained by a test sheet in the form of daily tests and direct observation conducted by 3 observers. The results obtained are the average value of the process skills of students in learning cycle I is 80.49 with the Good category and increase in the second cycle to 87.30 with the Good category. The average value of absorption of students in the first cycle was 72.60 with the Enough category and increased in the second cycle to 80.23 in the Good category. For student learning completeness in learning cycle I which is equal to 100% and cycle II has also reached 100% complete. The average value of attitudes of students in learning cycle I is 78.71 with the Enough category and increases in the second cycle to 81.97 with the Good category. Based on the results of the study it can be concluded that the application of the POE model (prediction, observation, explanation) can improve the process skills and learning outcomes of class VIII students of SMP N 14 Pekanbaru.Key Words: POE, process skills, learning outcomes